Planes - Royston, Angela, 1945- (New York : Aladdin Books, 1992)
Simple text, photographs, and illustrations depict different categories of airplanes, including light aircraft, passenger plane, biplane, and fighter plane.
"A Dorling Kindersley book."
Keywords: Airplanes -- Juvenile literature; Airplanes